Design Fabrication and Performance Evaluation of Multiband Aperture Coupled Microstrip Antenna - Garima (My University, 2013)
The main aim of the thesis work would be to increase the number of frequencies using single patch antenna and to increase the bandwidth. This can be done by cutting different shapes of slot in patch and by using different shapes of patch using aperture coupling feed used for wireless applications. The analysis of aperture coupled microstrip antenna is done using transmission line model. A simple rectangular microstrip patch antenna is designed using aperture coupling at 5.2 GHz used for WLAN frequencies and its parametric study is done to get the best results. Next, single U- slot is cut in the patch of simple aperture coupled antenna resonating at two WLAN frequencies 3.6 GHz, 5.2 GHz. Two U- slots in patch of simple aperture coupled antenna resonating at three WLAN frequencies 3.6 GHz, 5.2 GHz and 5.8 GHz. This will result in reducing the number of antennas as single antenna is resonating at two or three resonant frequencies. Also a triple and multiband S- shaped slotted patch antenna is designed using aperture coupling feed used for L- band applications like GPS, satellite communication etc. These antenna cover the L1 (1.575 GHz), L2 (1.227 GHz) and L5 (1.176 GHz) frequencies, which are required forwireless applications. The analysis of aperture coupled microstrip antenna is done using transmission line model. A simple rectangular microstrip patch antenna is designed using aperture coupling at 5.2 GHz used for WLAN frequencies and its parametric study is done to get the best results. Next, single U- slot is cut in the patch of simple aperture coupled antenna resonating at two WLAN frequencies 3.6 GHz, 5.2 GHz. Two U- slots in patch of simple aperture coupled antenna resonating at three WLAN frequencies 3.6 GHz, 5.2 GHz and 5.8 GHz. This will result in reducing the number of antennas as single antenna is resonating at two or three resonant frequencies. Also a triple and multiband S- shaped slotted patch antenna is designed using aperture coupling feed used for L- band applications like GPS, satellite communication etc. These antenna cover the L1 (1.575 GHz), L2 (1.227 GHz) and L5 (1.176 GHz) frequencies, which are required for differential GPS system in order to provide maximum position accuracy. The antenna also covers LQ (1.48 GHz) frequency for satellite broadcast. The broadband and dual band E- shaped patch antenna is designed using aperture coupled feeding technique. These antennas fulfil requirement of both broad bandwidth and increased number of frequencies using single patch aperture coupled microstrip antenna. The fabrication antenna is designed using aperture coupled feeding technique. These antennas fulfil requirement of both broad bandwidth and increased number of frequencies using single patch aperture coupled microstrip antenna. The fabrication of the single band antenna resonating at 5.2 GHz is done using VNA model no: E5071C. The testing results along with the comparison between testing results and simulated results is also shown.
Master of Engineering-Dissertation
Keywords: ACMA; U slot; S Slot; E slot; CST; WLAN; VNA; Multiband